SYSTEM OF WORK IN STATE ORGANIZATIONS AND ITS ECONOMIC ESSENCE (World Bulletin of Management and Law, 2022)
In this article, the system of working in state organizations is analyzed, besides, the economic significance of these processes is considered
Keywords: administration; information; management body